Penciptaan Busana Pesta Malam dengan Sumber Ide Palazzo Dandolo Venesia - Nura Muhaimin; Yuhri Inang Prihatina (Universitas Negeri Surabaya, 2026)
The purpose of this research is to create evening party wear with the idea of ​​Palazzo Dandolo Venice as the source of inspiration, especially for the masquerade ball event. Through the application of gothic ornamental motifs in the room and furniture, manipulation techniques of draping and embroidery, S, I and A silhouettes, the use of gold champagne and dark purple, as well as sequins and masks as clothing decoration. This research is motivated by the need for innovation in evening party wear design that not only emphasizes the aesthetic aspect, but also has cultural and historical value. The research method uses the Double Diamond Method which consists of four stages. In the discover stage, data related to Palazzo Dandolo is collected and explored, including historical, cultural, and visual aspects. The define stage is carried out by analyzing data in the form of colors, materials, silhouettes, and techniques such as draping and embroidery which are outlined in a moodboard. In the develop stage, alternative designs are created, the best design is selected, and a prototype is developed. Deliver the prototype refinement and presented in a fashion show. The novelty of this research lies in the use of Palazzo Dandolo as a source of ideas combined with the iconic Venetian masquerade ball culture. Originality or added value of technical innovation research through the application of embroidery and draping manipulation, which enriches the texture, visual dimension, and artistic details of clothing. The result of this research is a pair of mysterious yet elegant evening gowns typical of Palazzo Dandolo. Keywords:: evening wear, palazzo dandolo, Venice